Faktor Determinan Kasus Diabetes Mellitus Tipe 2 di Kabupaten Administrasi Kepulauan Seribu Provinsi DKI Jakarta Tahun 2023 - Darmawanti, Ulinuha Setya (UI Scholars Hub, 2024)
Kepulauan Seribu Administrative District has the highest Diabetes Mellitus Incidence Rate compared to other areas in the DKI Jakarta Province, which is 317.4 per 10,000 residents. The purpose of this research is to identify the determinant factors that most influence cases of Type 2 Diabetes Mellitus in the Kepulauan Seribu in 2023, based on the relationship between factors such as Age, Gender, Occupation, History of Diabetes Mellitus, Body Mass Index (BMI), Excessive Sugar Consumption, Excessive Salt Consumption, Excessive Fat Consumption, Insufficient Fruit and Vegetable Intake, and Lack of Physical Activity. This research employs an analytical observational study method with a case-control study design using secondary data, involving a sample size of 329 individuals as cases and 329 individuals as controls. Data analysis was conducted using univariate, bivariate, and multivariate analyses. The research results indicate that the determinant factors with a risk of causing Type 2 Diabetes Mellitus are age, occupation, body mass index, diabetes history, and excessive sugar consumption. The variable with the highest risk probability is a history of diabetes (odds ratio [OR] 49.346 [95% CI 25.2–96.3]). In addition to promotional, preventive, curative, and rehabilitative efforts, a collaborative approach through also needed to tighten regulations on high-sugar food and beverages in order to reduce the prevalence of diabetes mellitus in the future.